Redox-triggerable firefly luciferin-bioinspired hydrogels as injectable and cell-encapsulating matrices. Issue 35 (24th August 2022) - Jin, Minye; Gläser, Alisa; Paez, Julieta I.
Abstract : A novel redox-triggered bioinspired hydrogel platform that offers high control over gelation onset and kinetics is presented. This platform is suitable for the development of injectable matrices. Abstract : Stimuli-responsive hydrogels are smart materials that respond to variations caused by external stimuli and that are currently exploited for biomedical applications such as biosensing, drug delivery and tissue engineering. The development of stimuli-responsive hydrogels with defined user control is relevant to realize materials with advanced properties. Recently, our group reported firefly luciferin-inspired hydrogel matrices for 3D cell culture. This platform exhibited advantages like rapid gelation rate and tunability of mechanical and biological properties. However, this first molecular design did not allow fine control of the gelation onset, which restricts application as a cell-encapsulating matrice with injectable and processable properties. In this article, we endow the firefly luciferin-inspired hydrogels with redox-triggering capability, to overcome the limitations of the previous system and to widen its application range. We achieve this goal by introducing protected macromers as hydrogel polymeric precursors that can be activated in the presence of a mild reductant, to trigger gel formation in situ with a high degree of control. We demonstrate that the regulation of molecular parameters ( e.g., structure of the protecting group, reductant type) and environmental parameters ( e.g., pH, temperature) of the deprotection reaction can be exploited to modulate materials properties. This redox-triggerable system enables precise control over gelation onset and kinetics, thus facilitating its utilization as an injectable hydrogel without negatively impacting its cytocompatibility. Our findings expand the current toolkit of chemically-based stimuli-responsive hydrogels.